(3fMh JWHjb EdRGejI GdJYdje Ydi GdGhdGO ZjQ GdedJMbjf HGdeOQSI (B((3YeQ (B6 (3Gdi (B15 (3SfI (B)s - (3MWH , RgjQs ((3HjQhJs (3GdeQcR GdJQHhj ddHMhK hGdEfeGAs, 2014)
(3jMGhd GdJbQjQ OQGSI GdJCKjQ aj bQGQ GdJMGb GdChdGO GdPjf ge HYeQ GdOQGSI HGdeOQSI, hJMOjO MLe GdXGgQI hGdNUGFU GdOjehZQGajI hGdELJeGYjI daFGJ GdCWaGd hGdChdGO ZjQ GdedJMbjf HGdeOQSI hJMOjOkG GdaFI GdYeQjI ef (B6 (3Edi (B15 (3SfI, hJYjjf NUGFUgG ef MjK GdJhRY GdYeQj hGdLZQGaj hGdLfSj hGJLGgGJgG hehGbagG JLGg GdJYdje hGdYed GdeHcQ hGdJSqQH(B. (3jJchf eLJeY GdOQGSI ef (B220 (3CSQI dOjge ChdGO ef GdLfSjf JJQGhM CYeGQge Hjf (B6 (3h(B15 (3SfI ef GdedJMbjf hZjQ GdedJMbjf HGdeOGQS, ef LejY CfhGY GdeOGQS, GdQSejI, GdeLGfjI, hZjQ GdeLGfjI, aj LejY GdeMGaXGJ GddHfGfjI, Hjf GdaJQI GdeeJOI ef (B2001 (3Edi (B2011. (3EJHYJ GdOQGSI KdGKI efGgL, GdEMUGFj, GdGSJWdGYj hGdbGfhfj, aGSJNOeJ GdEMUGAGJ hGdOQGSGJ GdSGHbI ceUOQ dJLejY GdHjGfGJ, hcPdc COGI GdedGMXI, GdESJeGQI hGdebGHdI(B. (3HqjfJ GdfJGFL Cf GdGdJMGb HGdeOGQS GddHfGfjI gh GdJMGb ZjQ eJhGRf Hjf GdCWaGd GdPjf jdJMbhf HGdUa GdChd ef eQMdJj GdQhVI hGdMdbI GdChdi, Cj Cnqf JdejPG hGMOG ef Hjf cd (B6 (3JdGePI HYeQ GdOQGSI jdJMbhf dChd eQI HGdeOQSI GdQSejI, hbO GSJeQ gPG GdhGbY HGfJXGe aj GdSfhGJ GdCNjQI(B. (3cPdc YOO GdChdGO GdPjf jHdZhf Sf GdEdJMGb HGdeOGQS SfhkqjG HMSH bGfhf GdEdRGejI jUd Edi bQGHI NeSI BdGa Wad aj LejY GdCQGVj GddHfGfjI(B. (3ceG JHjf Cf fSHI cHjQI ef GdCgGdj HGOQJ Edi EdMGb CHfGFgG HGdeOGQS GdQSejI ef YeQ (B4 (3SfhGJ Cj HUaha GdQhVI, hdjS ef YeQ (B6 (3SfhGJ Cj Uaha GdMdbI GdChdi(B. (3hXgQ aj LejY GdefGWb Cf GdGdJMGb HGdMdbJjf GdChdi hGdKGfjI jUd JbQjHG Edi eSJhi GdETHGY, dcf JJahb fSHI JSLjd GdPchQ Ydi GdEfGK(B. (3HGdEVGaI Edi WHjYI GdeOf GdJj JTcd YGedG eDKQG ddJSQH(B.s
(3GdfhY (B: (3JbQjQs
Keywords: Basic Education; Compulsory Education; Enseignement de base; Enseignement Obligatoire; (3GdJYdje GdCSGSjs; (3GdRGejI GdJYdjes